Determinants of Unemployment Among Gen Z in South Sulawesi - Ayu, Sri Jayanti Dewa; Diksa, I Gusti Bagus Ngurah (Jurnal Ketenagakerjaan, 2024)
Indonesia has experienced a demographic bonus since 2015 with the peak period estimated to occur between 2020 and 2035, which is characterized by the population structure being dominated by people of productive age compared to non-productive age. The demographic bonus can be used as an opportunity for the government to improve its regional economy. According to the 2023 Indonesian Youth Statistics, the estimated percentage of youth (population aged 16 - 30 years) in Indonesia is 23.18 percent or almost a quarter of the Indonesian population. Still, the youth open unemployment rate (TPT) is also high, exceeding the national TPT. The 2020 Population Census portrait shows that youth in Indonesia are dominated by Generation Z (Gen Z) with a total population of 74.93 million. Data from the Central Statistics Agency (BPS) shows worrying figures regarding unemployment among Gen Z in Indonesia. As many as 9.9 million Gen Z aged 15-24 years will be recorded as unemployed in 2023, which is equivalent to 22.25% of the total Gen Z population in Indonesia. Gen Z is a population group that dominates the population composition of South Sulawesi and has the potential to become an actor in Indonesia's future development. The analytical method used in this research is binary logistic regression. The results of this study show that the variables gender, marital status, head of household status, education level and type of region have a significant influence on the emergence of unemployment among Gen Z.